PERIODONTAL PHENOTYPE: A CLINICAL AND CURRENT VIEW - Lucas Mendes Gabri; Victor Gila Gomes de Mattos; Luis Paulo Diniz Barreto; Marcela Melo dos Santos (Portal de Periódicos da Marinha do Brasil, 2021)
One of the essential elements to achieving smile esthetics is the phenotype and gingival contour, which with their architecture influence the size of dental crowns. The term "periodontal phenotype" was standardized in the 2017 World Workshop on the Classification of Periodontal and Peri-Implant Diseases and Conditions. However, much has been said about the topic, with other nomenclatures. Evaluating different periodontal phenotypes is essential, as they provide us with information related to the characteristics of periodontal tissues and dental forms. In addition to making the treatment more predictable, it can avoid problems such as trauma, inflammation, and other clinical and surgical complications. The purpose of this literature review is to research the topic, periodontal phenotype, through the most relevant articles between the period 2017 to 2021, showing its classification, prevalence, and forms of diagnosis. There are several ways to diagnose the periodontal phenotype, and the one recommended by the World Workshop is the transparency of the gingival sulcus using the millimeter probe. We can observe a prevalence of the thin phenotype for the female gender, whereas the thick phenotype is prevalent for the male gender. There is still a lack of scientific evidence for the correct relationship of the periodontal phenotype with other factors such as age, smoking, hygiene habits, diet and, malocclusion.